The Ordinary Contested, Laruelle contra Deleuze and Guattari. - Sackin-Poll, Andrew (Paragraph, 2021)
This article addresses the question of the relationship between corporeality and the ordinary in the works of François Laruelle. This is done through the formulation of the 'ordinary body' that draws from across Laruelle's work on the ordinary, corporeality and photography in order to outline Laruelle's radically immanent account of embodiment. The critical outline of Laruellean corporeality and the ordinary body is drawn out via a critical posing of Laruelle in contrast to Deleuze and Guattari. In doing so, the article indicates the singular difference between Laruelle, on one side, and Deleuze and Guattari, on the other, with respect to corporeal immanence and the usage of the everyday and ordinary. The article concludes with an argument that the relationship between the body and the ordinary in Laruelle's thought implies a novel non-philosophical or non-standard 'poetics' and usage of the ordinary.